1993
DOI: 10.1126/science.8456317
|View full text |Cite
|
Sign up to set email alerts
|

Activity-Dependent Regulation of Conductances in Model Neurons

Abstract: Neurons maintain their electrical activity patterns despite channel turnover, cell growth, and variable extracellular conditions. A model is presented in which maximal conductances of ionic currents depend on the intracellular concentration of calcium ions and so, indirectly, on activity. Model neurons with activity-dependent maximal conductances modify their conductances to maintain a given behavior when perturbed. Moreover, neurons that are described by identical sets of equations can develop different prope… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
289
0

Year Published

1998
1998
2021
2021

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 302 publications
(290 citation statements)
references
References 18 publications
1
289
0
Order By: Relevance
“…This question is particularly interesting in the light of recent experimental and theoretical studies of homeostasis of cellular and synaptic properties in the nervous system (Stemmler and Koch, 1999;Turrigiano, 1999;Marder and Prinz, 2002;Turrigiano and Nelson, 2004). These studies suggest that the intrinsic excitability of single neurons and synaptic strengths are subject to slow homeostatic regulation that can stabilize neuronal function despite ongoing turnover of channels and receptors (LeMasson et al, 1993;Turrigiano et al, 1995;Davis and Goodman, 1998;Liu et al, 1998;Desai et al, 1999;Golowasch et al, 1999a,b;Davis and Bezprozvanny, 2001;Aizenman et al, 2003;MacLean et al, 2003;Zhang and Linden, 2003). However, what really matters for the animal is not what the properties of single neurons are or how strong single synapses may be, but how the network performs.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This question is particularly interesting in the light of recent experimental and theoretical studies of homeostasis of cellular and synaptic properties in the nervous system (Stemmler and Koch, 1999;Turrigiano, 1999;Marder and Prinz, 2002;Turrigiano and Nelson, 2004). These studies suggest that the intrinsic excitability of single neurons and synaptic strengths are subject to slow homeostatic regulation that can stabilize neuronal function despite ongoing turnover of channels and receptors (LeMasson et al, 1993;Turrigiano et al, 1995;Davis and Goodman, 1998;Liu et al, 1998;Desai et al, 1999;Golowasch et al, 1999a,b;Davis and Bezprozvanny, 2001;Aizenman et al, 2003;MacLean et al, 2003;Zhang and Linden, 2003). However, what really matters for the animal is not what the properties of single neurons are or how strong single synapses may be, but how the network performs.…”
Section: Introductionmentioning
confidence: 99%
“…There is experimental evidence that stability of pyloric neuron activity results from activity-dependent homeostatic regulation, both at the level of single neurons (Turrigiano et al, 1994), and on the network level Simmers, 1998, 2000;Golowasch et al, 1999b;Luther et al, 2003). Previous theoretical work has shown that simple homeostatic rules in which Ca 2ϩ concentrations are used to track activity patterns can regulate both intrinsic properties and synaptic strengths (LeMasson et al, 1993;Liu et al, 1998;Golowasch et al, 1999b;Soto-Trevino et al, 2001).…”
Section: Stability Of Network Output With Different Network Configuramentioning
confidence: 99%
“…If channel densities are functionally linked to neuronal activity, as suggested by modeling studies (LeMasson et al 1993;Liu et al 1998), it can be imagined that activity bouts arise as channel densities are altered. An incremental change in one or more membrane conductance may allow a temporary resumption of the pyloric rhythm, but further changes in membrane conductances could result in the network falling silent again.…”
Section: Bout Propertiesmentioning
confidence: 99%
“…These are often understood in terms of context-and history-dependent slow modulations of neural response parameters. Several underlying molecular mechanisms support these modulations in an activity-dependent manner (LeMasson et al, 1993;van Ooyen, 1994;Marom, 1998;Wang, 1998;Carr et al, 2003). Such mechanisms are usually understood to operate by adding uniquely defined slow time scales (Marom and Abbot, 1994;Fleidervish et al, 1996;Kim and Rieke, 2003) and cannot capture multiple-time-scale dynamics.…”
Section: Introductionmentioning
confidence: 99%